Essays on applied microeconomics and development income risk, income shocks and household financial decisions : evidence from rural Vietnam - Wainwright, Fiona (Trinity College (Dublin, Ireland). Department of Economics, 2012)
Income risk remains a significant obstacle to rural development. Even within a transitioning economy such as Vietnam which has a significant social safety-net, income shocks (for example, natural disasters, illness, pest infestation, livestock disease) can be a cause of poverty and ruin for rural agricultural households. This thesis uses micro-theoretical foundations to empirically investigate the relationships between each of 1) social capital; 2) income risk and 3) income shocks and their impacts on household capacity to develop within a rural Vietnamese context. More specifically, this thesis contributes to the development literature concerned with 1) the role of social capital and its association with positive household formal financial services demand outcomes; 2) the various risk-coping strategies employed by households to deal with categories of income shocks and how this impacts upon household asset holdings and food consumption and 3) the impact of income risk on household investment and savings behaviour and associated household profit impacts.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin.